الشراكة بين الأمم المتحدة والاتحاد الأوروبي في تسوية الصراعات بعد الحرب الباردة (1990-2018) (Economic studies journal, 2019)
This study seeks to address the issue of partnership and cooperation between the United Nations and the European Union during the period( 1990 – 2018). Some political variables that occurred during and after the Cold War have been identified and have had an impact on the development of relations between the UN and regional organizations. Study of the Charter of the UN, which clarifies the relations between international bodies and institutions nd monitoring developments between the UN and the EU in the area of conflict resolution in the regions. Following up some aspects of the partnership between the UN and the EU after the Cold War like the meetings held between the two parties, the resolutions and declarations issued between them. Monitoring the EU's civil and military activities and operations in conflict resolution with the UN, beginning with Artemis in the Democratic Republic of the Congo and ending with the 2017 European Union Mission in Iraq. As well as the EU's financial contribution to peace and peace-building operations in several regions of the world was clarified. .